Fortidens fremtid - Welz, Claudia (Dansk Teologisk Tidsskrift, 2011)
How are we to relate to the past, especially to those events in the past which are hard to bear in the present? This is an ethical question that concerns the conditions and limits of our interactions with others. The article tries to clarify (1) what it is that we can remember, (2) what it is that we in any case must remember, and (3) what it is that we may forget, and in which situations this applies. Memory is investigated via negativa in investigating that which seems to negate memory, namely forgetting. However, the investigation of the legitimacy and questionability of forgetting shows that memory and forgetting are not just opposed, but also dialectically related to each other. Their dialectical interrelation is decisive for the formation and preservation of personal identity. Nonetheless, the future of the past is not to be found in human powers of remembrance or forgetting.